Edukasi Ilmu Faraid Dalam Upaya Menyelesaikan Masalah Warisan Pada Masyarakat Kota Metro - Arif Budiman; Taufid Hidayat Nazar; Rahmah Ningsih; Muhammad Fauzhan ‘Azima (Institut Agama Islam Sumatera Barat, 2023)
Faraid science is a part of knowledge about religion that has not received attention in society. This educational activity is expected to be able to provide an understanding of the basic concept of conflict-prone inheritance distribution in society. The partners assisting this educational activity are the people of Metro City who are actively participating in the Payungi Entrepreneurial Islamic Boarding School program. This community is a representation of the people of Metro City who have been equipped with the basics of religious knowledge. The method of implementing community service uses lecture and practical methods. After the delivery of the basic material of Faraidh Science, a post test was carried out and an evaluation was made of the participants' understanding. The result of this service activity is that the people of Metro City can understand the basic concepts of Faraidh Science and laws related to Islamic inheritance. In addition, the people of Metro City are able to map heirs and determine the share of inheritance within the family and are able to apply the technical division of inheritance internally.